Review of Research on Samkok in Thailand - Jin, Yong (Journal of Sinology (วารสารจีนวิทยา), 2010)
Chaophraya Phraklang(Hon)’s version of Samkok, the first Thai translated version of The Romance of the Three Kingdoms appeared in 1802, it had a dramatic impact on the development of the Thai literature and the social formation of Thailand. Thai researchers show great concern for the Samkok research. The main purpose of this paper is to know the paradigm and status of Samkok research in Thailand through reviewing those Samkok research findings systematically. gorgeous adornment, marvelous embroidery, unique designs, and excellent craftsmanship. The purpose of this paper is to use several types of theatrical costume pieces as a means to understand the visual language of the theatrical costumes employed in the gala performances during the Qianlong reign and the ways in which these theatrical attires “communicated” with the court audiences during the gala performances, which reflected the overall context of the court theater during the Qianlong era.